EVALUATING STRATEGICAL SPATIAL PLANNING APPROACH IN CASE OF ISTANBUL - Sinan LEVEND; Rahmi ERDEM (European Regional Science Association (ERSA), 2011)
In Turkey, The law of Institutional Strategic Planning (ISP) issued in order to compliance with European Union is unfortunately insufficient recovering spatial-oriented strategic planning (SSP) decisions. There is not a fundamental Spatial Strategic Planning model based on strategic spatial planning and an integrated structure that can be coordinated with both the strategic plans prepared by municipalities and strategic plans prepared by the government. Strategic Spatial Planning (SSP) process that sub-units have to correspond is not clearly defined although the Public Strategic Plan is mandatory by the legal regulation. İstanbul as a metropolis has got a lot of urbanization problems. Its operational planning boundaries surpasess its provincial boundaries. It exposes to a high level of risk because of earthquake, and its natural and cultural values are under threat because of rapid urbanization. The need for a planning organization that is taken as a whole up to the scale of urban design, transparent, comprehensive participated, cooperative and continuous is the major undisputed fact. This paper aims to evaluate SSP approach in Turkey in the case of İstanbul. For this purpose, firstly a literature review is conducted to define Strategical Planning. Eventually, in Istanbul Institutional Strategical Planning and Environment Arrangement Planing (100000 scale) are analyized and these plans are evaluated in terms of adequacy of strategical planning approach.
Keywords: 330; strategic; strategical spatial planning; İstanbul